14m+2n-6m+10n=

Simple and best practice solution for 14m+2n-6m+10n= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14m+2n-6m+10n= equation:


Simplifying
14m + 2n + -6m + 10n = 0

Reorder the terms:
14m + -6m + 2n + 10n = 0

Combine like terms: 14m + -6m = 8m
8m + 2n + 10n = 0

Combine like terms: 2n + 10n = 12n
8m + 12n = 0

Solving
8m + 12n = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-12n' to each side of the equation.
8m + 12n + -12n = 0 + -12n

Combine like terms: 12n + -12n = 0
8m + 0 = 0 + -12n
8m = 0 + -12n
Remove the zero:
8m = -12n

Divide each side by '8'.
m = -1.5n

Simplifying
m = -1.5n

See similar equations:

| P=380mw+20 | | 130=70+4y | | 2(7x-5)+3=5(3x+2)-4 | | 8r-5=45-2r | | 15x(4+8)-33=153 | | 10x+4x+4+8=3x+3+10x | | 4+7z=20+-3z | | 7x+3x-5x= | | x+2(x+4)=39 | | 9-1=b | | (21b-7)-5(4b+4)=-5 | | 7x-(x+4)-(2x+1)=10 | | Y=3x+1+3 | | Y=3x+1+1 | | 7y+7/3=4 | | 5x+-10=9x+26 | | -10+7x+1=46 | | 75=3(-10t-3)+5t | | 5t=42-t | | 2a=20-2a | | 28x+12=21+19x | | (110-8x)=3x | | f(41f-43)=0 | | 3(3x+7)=18 | | -7(6+8n)=-14 | | n^2+n+12=0 | | 425+25x=275+30y | | 1/5z+z+9=-9 | | 9x=9x+12 | | x^2+3x-2=x | | X=14x+1500 | | ln(3)+ln(x)=8.94 |

Equations solver categories